Acinar Gland Hyperplasia Masquerading as Pancreatic Head Carcinoma: A Case Report on a Diagnostic and Surgical Dilemma - Prima Maulana Cahyo Nugroho; Suryo Wahyu Raharjo (Open Access Indonesian Journal of Medical Reviews, 2025)
The preoperative differentiation of benign from malignant pancreatic head masses presents a significant clinical challenge. While pancreatic ductal adenocarcinoma (PDAC) is the primary concern, rare benign pathologies can be radiologically and clinically indistinguishable from cancer, leading to diagnostic uncertainty and complex surgical decisions. A 61-year-old male presented with a classic triad of obstructive jaundice, significant weight loss, and right upper abdominal pain. A contrast-enhanced computed tomography (CT) scan of the abdomen revealed a solid mass in the head of the pancreas, causing concomitant dilation of the common bile and pancreatic ducts—the "double duct sign." These findings were highly suggestive of pancreatic head carcinoma, prompting a decision for surgical intervention. The patient underwent a standard pancreaticoduodenectomy (Whipple procedure). Surprisingly, the final histopathological examination of the resected specimen revealed no evidence of malignancy. The diagnosis was benign acinar gland hyperplasia. The postoperative course was complicated by a delayed post-pancreatectomy hemorrhage from a gastroduodenal artery pseudoaneurysm, which was successfully managed with minimally invasive transarterial embolization (TAE). In conclusion, acinar gland hyperplasia is an exceedingly rare benign condition that can precisely mimic the clinical and radiological features of pancreatic cancer. This case underscores the current limitations of preoperative diagnostics and affirms that aggressive surgical management is justified in patients with a high suspicion of malignancy, as the risk of withholding surgery for a potentially curable cancer outweighs the risk of resecting a benign lesion. Furthermore, it highlights that the Whipple procedure carries a significant risk of life-threatening complications, such as delayed hemorrhage, irrespective of the underlying pathology, necessitating vigilant postoperative care.